(untitled) (Archives of Clinical Psychiatry, 2015)
Background Ghrelin is a potent hormone with central and peripheral action. This hormone plays an important role in the regulation of appetite, food intake, and energy balance. Studies have suggested that ghrelin is involved with eating disorders (ED), particularly bingeing and purging. Genetic variants have also been studied to explain changes in eating behavior. Methods We conducted a literature review; we searched PubMed, Scientific Electronic Library Online (SciELO), and LILACS databases using the keywords “eating disorder”, “ghrelin”, “polymorphism”, “anorexia nervosa”, “bulimia nervosa”, “binge eating disorder”, and their combinations. We found 319 articles. Thirty-nine articles met the inclusion criteria. Results High levels of ghrelin were found in patients with anorexia nervosa (AN), especially in the purging subtype (AN-P). There was also a positive correlation between fasting ghrelin level and frequency of episodes of bingeing/purging in bulimia nervosa (BN) and the frequency of bingeing in periodic binge eating disorder (BED). Some polymorphisms were associated with AN and BN. Conclusion Changes in ghrelin levels and its polymorphism may be involved in the pathogenesis of EDs; however, further studies should be conducted to clarify the associations.